2009
DOI: 10.1007/s12197-009-9084-4
|View full text |Cite
|
Sign up to set email alerts
|

On the financial characteristics of firms that initiated new dividends during a period of economic recession and financial market turmoil

Abstract: Dividend Initation, Recession, Financial Market Turmoil, G 14, 32, 35,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In total, 65 dividend initiating firms (DIF) are matched randomly with 65 firms from the same industry to find financial profiles that can predict new DIF in a future economic downturn (Payne, 2009). Payne found "the greater the following: cash flow per share, price stability, earnings predictability, and return to total capital, the more likely the firm would initiate new dividends […]" (Payne, 2009). The larger the ratio of market value to book value, the less chance of a firm becoming a DIF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 65 dividend initiating firms (DIF) are matched randomly with 65 firms from the same industry to find financial profiles that can predict new DIF in a future economic downturn (Payne, 2009). Payne found "the greater the following: cash flow per share, price stability, earnings predictability, and return to total capital, the more likely the firm would initiate new dividends […]" (Payne, 2009). The larger the ratio of market value to book value, the less chance of a firm becoming a DIF.…”
Section: Introductionmentioning
confidence: 99%
“…The converse is not stated. Instead it is concluded that the ratio of market value to book value "was not a characteristic of DIF" (Payne, 2009). Payne's purpose was to find a financial profile for DIF that can be used for predicting future DIF in a new financial period of distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study will focus attention on firms with low liquidity ratios and high debt ratios looking for similar results. Payne (2009) establishes a unique financial profile for dividend initiating firms during the most recent recession. A surprise was the ratio of market value to book value was not a characteristic of dividend initiating firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Payout decisions boil down to the opportunity expectations and preferences of managers and owners (with their own principal-agent related problems), as well as to how the decision will be perceived by other stakeholders (Below and Johnson, 1996;Golden and Kohlbeck, 2017). According to Fuller and Goldstein (2011) and Payne (2011), the revealing role of dividend decisions is further emphasised in declining markets, which allow to draw conclusions on reserves, future expectations, but also on the quality of corporate governance (Attig et al, 2016;Mehdi et al, 2017). In an uncertainty environment, dividend payout decisions are even more interesting, because without known risk distributions providing guidance, the potential of loss-taking for the company and the commitment of the owners to it become the dominant factors in these decisions (Hauser, 2013;Welker et al, 2017), besides an increasing stakeholder pressure on certain industries.…”
Section: Introductionmentioning
confidence: 99%